ANALYSIS OF THE EFFECT OF INVENTORY INTENSITY, PROFITABILITY, AND SALES GROWTH ON TAX AVOIDANCE (EMPIRICAL STUDY OF NON-CYCLICAL CUSTOMERS FOR THE PERIOD 2022-2024) - Elsa Felicia; Linda Santioso (International Journal of Application on Economics and Business, 2026)
his research investigates the influence of inventory intensity, profitability, and sales growth on tax avoidance among non-cyclical sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2022–2024. Employing purposive sampling, 138 firm-year observations were obtained from secondary data sourced from the IDX’s official website www.idx.co.id and company websites and respective company websites. The data analysis includes descriptive statistics, classical assumption tests, and multiple linear regression with SPSS version 31. The results reveal that sales growth exerts a significant negative effect on tax avoidance, profitability has a significant positive effect, while inventory intensity demonstrates no significant relationship. These findings provide empirical evidence on the varying impacts of firm characteristics on tax avoidance, offering insights for policymakers, investors, and corporate stakeholders.